Assessing public perception and awareness of UK mandatory calorie labeling in the out‐of‐home sector: Using Twitter and Google trends data - Megan Polden; Eric Robinson; Andrew Jones (Wiley, 2023)
Abstract Objectives In 2021 the UK government announced a new obesity policy requiring large out‐of‐home food outlets to provide mandatory in‐store calorie labeling on food and drink items. Public acceptability and engagement with obesity policies could influence the level of impact on wider public health particularly with population‐level policies such as calorie labeling. This study aimed to examine public responses and awareness of the policy using social media (Twitter) comments and Google trends data. Methods This study examined responses to social media posts on Twitter (tweets) from the UK Department of Health and Social Care detailing the policy, implementation date and post‐implementation information about the policy's enforcement. The sentiments of the tweets were coded and the number of likes and replies extracted. This study utilized google trends to examine public awareness of the policy by extracting weekly relative search volume for relevant phrases such as "calorie labeling." Results From the 276 replies/quote‐tweet extracted, the majority expressed a negative sentiment toward the policy (N = 197/71.4%). There were fewer tweets expressing a positive sentiment (N = 25/8.7%) and a neutral/no sentiment (N = 54/19.6%). There was no difference in the number of "likes" or retweets between tweets expressing positive or negative sentiments. Five themes were identified expressing negative sentiments (most common being negative impacts on eating disorders). Google trends data revealed increased searches for "calorie labels/labeling" during the week of the policy enforcement compared to previous weeks in the last 5 years but no significant differences in searches for specific menu calorie labeling. Conclusions This analysis revealed negative sentiment toward and increased searching of calorie labeling information during the announcement and implementation of the 2021 mandatory calorie labeling policy in England. A greater understanding of public responses to calorie labeling policies may help tailor future policies and public communication strategies.